The Effect of Nutrition, Iron and Folic Acid Consumption with Incidence of Anemia in Pregnancy - Indrawati, Iing Yuli; Puspitasari, Yenny; Indasah, Indasah (JURNAL KEBIDANAN, 2023)
Anemia in pregnancy is a risk factor for bleeding. Anemia in pregnancy is a health problem that has a negative impact on pregnancy. According to WHO, the prevalence of anemia in pregnancy is 18% in developed countries and 35-75% in developing countries. This research is an analytical observational study with a cross sectional design on 115 pregnant women in Pamekasan District. Data collection used a data collection format, questionnaire, samples were taken using the simple random sampling method. Data analysis using logistic linear regression test. Based on the results of the logistic linear regression analysis, it shows that with a p-value <0.05, H1 is accepted. There is a significant effect of iron tablet consumption on the incidence of anemia in pregnant women with a p value of 0.048 <0.05. There is a significant effect of folic acid consumption on the incidence of anemia in pregnant women with a p value of 0.048 <0.05. There is an influence between the nutritional content of food on the incidence of anemia in pregnant women with a p value of 0.032 <0.05. The three variables together have an influence on the incidence of anemia in pregnant women. There is an influence of consumption of iron tablets on the incidence of anemia in pregnant women and there is a statistically significant influence of consumption of folic acid on the incidence of anemia in pregnant women in the Pegantenan Community Health Center area. So, based on the research results, it can be concluded that there is an influence of consumption of iron and folic acid tablets and the nutritional content of food on the incidence of anemia in pregnant women.